2015
DOI: 10.3390/w7052082
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Oscillations Intrinsic to Water: Applications to Cellular Time Keeping and Water Treatment

Abstract: Abstract:A homodimeric, growth-related and time-keeping hydroquinone oxidase (ENOX1) of the eukaryotic cell surface capable of oxidizing intracellular NADH exhibits properties of the ultradian driver of the biological 24 h circadian clock by exhibiting a complex 2 + 3 set of oscillations of copper salts and appear to derive from periodic variations in the ratio of ortho and para nuclear spins of the paired hydrogen atoms of the elongated octahedral structure of the ENOX1 protein bound copper II hexahydrates. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…5,17 There are several attempts of theoretical explanation 18 for such spin conversion mechanisms. Spin isomers are expected to generate periodical and quasiperiodical oscillations with different periods in biochemical reactions 19 and biological organisms. 20 The topic of spin conversion/ reorientation under energy flux is not new, for instance, similar mechanisms in singlet oxygen are well investigated in application to chemical and biological processes.…”
mentioning
confidence: 99%
“…5,17 There are several attempts of theoretical explanation 18 for such spin conversion mechanisms. Spin isomers are expected to generate periodical and quasiperiodical oscillations with different periods in biochemical reactions 19 and biological organisms. 20 The topic of spin conversion/ reorientation under energy flux is not new, for instance, similar mechanisms in singlet oxygen are well investigated in application to chemical and biological processes.…”
mentioning
confidence: 99%
“…Our findings do not directly answer the question of what is the fundamental period length of the ortho/para oscillations of water that appear to generate the ultradian rhythm suggested to underlie the biological clock. The actual period of the individual oscillations may be in the order of about 6 sec which, by a process of algebraic summation, would generate higher order oscillations the sum of which are no longer sinusoidal and give rise to "super" periods to generate a "composite wave" with an observed period length of 286 (12 sec × 24=288 sec) sec and ultimately the 1130 sec (18.8 min) period correlated with biological activity [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported evidence that properties inherent in the structure of water relate to phenomenon of biological rhythms as underlying the mechanism responsible for the characteristic periodic oscillations [2]. For such mechanisms to be oscillatory, transitions between different states of water must first of all be synchronous.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations